A decision support tool to mitigate decision-making problems faced by a building design team. Issue 1 (3rd April 2017) - Singhaputtangkul, Natee
Abstract : Purpose: There are a number of decision-making problems encountered by a building design team. This issue is apparent in assessment of building envelope materials and designs in the early design stage. The purpose of this paper is to develope a decision support tool based on a quality function deployment (QFD) approach integrated with a knowledge management system (KMS) and fuzzy theory to facilitate a building design team to simultaneously mitigate the decision-making problems when assessing the building envelope materials and designs for the first instance. Design/methodology/approach: This study engaged a design team comprising three decision makers (DMs) to test the developed decision support tool through a case study of a representative building project. The study employed deductive qualitative data analysis with use of a framework analysis approach to analyze perspectives of the DMs after completing the case study through a semi-structured interview. Findings: A mapping diagram derived qualitatively from the framework analysis suggested that the tool can help mitigate the identified decision-making problems as a whole. Originality/value: Practical contributions of using the decision support tool include achievement of a more efficient design and construction management, and higher productivity of a project. In terms of academic contributions, this study expands capabilities of a conventional decision support system, KMS, and QFD tool to handle decision-making problems.